2006
DOI: 10.1038/sj.ejcn.1602368
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant vitamins E and C as adjunct therapy of severe acute lower-respiratory infection in infants and young children: a randomized controlled trial

Abstract: Objective: To evaluate the effect of antioxidant Vitamins E and C as adjunct therapy of severe acute lower respiratory infection (ALRI) in children. Design: Randomized double-blind placebo-controlled clinical trial. Setting: A large childrens' hospital serving the urban poor in Kolkata, India. Subjects: Children aged 2-35 months admitted with severe ALRI. Intervention: In total, 174 children were randomly assigned to receive a-tocopherol 200 mg and ascorbic acid 100 mg twice daily or placebo for 5 days. All ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…In the previously described prophylactic study in India, supplementation of children who had severe respiratory illness with vitamins C and E did not influence the duration of the illness or any indicators of severity such as fever, feeding difficulty, or tachypnea. 177 The lack of effect observed in this study is consistent with findings from studies of therapeutic vitamin C supplementation; the therapeutic use of vitamin E supplementation at the onset of infections has not been examined.…”
Section: Other Infectionssupporting
confidence: 81%
See 1 more Smart Citation
“…In the previously described prophylactic study in India, supplementation of children who had severe respiratory illness with vitamins C and E did not influence the duration of the illness or any indicators of severity such as fever, feeding difficulty, or tachypnea. 177 The lack of effect observed in this study is consistent with findings from studies of therapeutic vitamin C supplementation; the therapeutic use of vitamin E supplementation at the onset of infections has not been examined.…”
Section: Other Infectionssupporting
confidence: 81%
“…176 Several RCTs have examined the effects of supplementation with vitamins in combination on the DTH response. In a therapeutic trial in India, 174 children 2 to 35 months of age who had been admitted to a hospital with acute lower respiratory infection were randomized to receive either a combination of vitamins C (100 mg) and E (200 mg) or a placebo twice daily for 5 days 177 (Table 4; please go to www.ilsi.org/Publications/ NutritionReviews/). The DTH response to seven antigens was assessed on admission and 2 weeks later.…”
Section: Delayed Type Hypersensitivity Responsementioning
confidence: 99%
“…Studies on the efficacy of zinc supplements in reducing the duration of pneumonia have shown conflicting results and as far as we know, no metaanalysis has been conducted on the effect of zinc on acute pneumonia. The use of the antioxidant vitamins E and C as adjunct therapy in children with severe ALRI has also been shown to have no benefit (52). While the benefits of a single micronutrient may be equivocal, a multi-micronutrient supplement as used in the current study may be more beneficial in HIVinfected children.…”
Section: Discussionmentioning
confidence: 76%
“…11 The effect of vitamin C and E on the immune system can also be explained by increasing the number of lymphocyte proliferation, and rising in interferon production that has an antiviral infection role. 12 Vitamin C is a co-factor that speeding up the hormone production and immune potentiation including its effect on the anti-viral immune responses through the production of interferon-a/b at the initial stage of influenza A virus (H3N2) infection. 13 Vitamin C and E deficiency has been considered to impair adaptive immune system both humoral and cellular immunity.…”
Section: Vitamin C and Ementioning
confidence: 99%
“…18 On the other hand, vitamins C and E had no benefit in children who suffered from pneumonia. 12 There have been many studies evaluated the effects of these vitamins in the incidence, duration and severity of common cold, both as prevention or treatment. 19 Consuming vitamin C did not prevent of having this disease, 7 even in heavy physical activity people.…”
Section: Role Of Vitamins C and E On Respiratory Infectionsmentioning
confidence: 99%